Crime concentrations and micro places: An empirical test of the "law of crime concentration at places" in Belgium. Issue 3 (September 2019) - Hardyns, Wim; Snaphaan, Thom; Pauwels, Lieven JR
This study examines the extent to which crime concentrations occur at micro places, in order to test Weisburd's law of crime concentration at places, in two large Belgian cities. Police-registered crime data for the period 2004–2012 were used. Analyses were conducted at the grid level (using 200 meters by 200 meters grid cells), as a proxy for behavior settings. This study assesses Weisburd's theoretical proposition and by (partly) replicating prior empirical research, we conclude that the findings are in line with those from prior studies regarding crime concentration at micro places. Finally, opportunities and avenues for future research on crime places are discussed.